William Taylor, Peninsular War surgeon and deputy inspector of hospitals at Waterloo. (February 2023) - Cooper, Max; Whiston, Ben; Fernandes, Carl
William Taylor was a British army surgeon remembered for his role as deputy inspector of hospitals (DIH) at Waterloo serving under Sir James Grant MD (1778–1852). No biography of Taylor exists beyond his entry in Drew's records of commissioned officers in the medical services of the British Army. Taylor appears to have been a Scotsman and is first noted as a hospital mate in 1795. He joined the 10th Royal Dragoons (Hussars from 1806) as an assistant surgeon in 1797. He is recorded at Guildford (1800) and Brighton (1803). He was made surgeon in August 1803. A further reference to Taylor, deduced from the title of "regimental surgeon, " is documented at Lewes, Sussex, in 1808. Taylor served with the 10th Hussars in the Peninsular and Challis' roll call records his service at the Battles of Sahagún (21 December 1808) and Benavente (29 December 1808). Taylor was transferred to the staff on 20 June 1811 and made DIH on 25 July 1811. He was put on half-pay before being reinstated for Waterloo. Taylor retired on half-pay in February 1816 and died at Turnham Green on 9 January 1820. His Waterloo medal was sold in 2006.